The true vine and the branches: Exploring the community ideation in John 15:1–16:3 - Gharbin, Godibert K. (Verbum et ecclesia, 2023)
An exploration of the Johannine narrative reveals that John addresses the problem of the relational dimension of a believing community as one of its ‘authorial intentions’. With its concomitant emphasis on communalism, the characterisation of community in John 15:1-16:3 makes it legitimate to propose that it is one of the narratives that address this problem. Therefore, the article aimed to contribute to the discussions on the Johannine community, focusing preponderantly on how the vine metaphor guides the reader to explore the community theme as the Johannine prescription for this sociocultural malady. The study employed a narratological analysis because it studies the poetics and meaning of the narrative, thereby helping to recreate the theological ideation of community in the narrative. The findings indicated that a believing community is defined by its relationship with Christ - the vine - and its concomitant incarnation of the divine community’s communalistic values. It also established that the incarnation of these collectivistic values in the believing community is a product of a divine-human partnership: the members of the divine and believing communities perform various roles, corporately and idiosyncratically to fulfil this mission. Intradisciplinary and/or interdisciplinary implications: The portrayal of the believing community in John 15:1-16:3 redefines a community as people participating in the divine community and reflecting its values, replacing the anthropocentric and anthropological characterisation of community with a theocentric classification. Consequently, the research intersects with the disciplines of anthropology and sociology.